(untitled) (Al-Qamar, 2020)
Colonel Muhammad Khan (1910-1999) is one of the renowned writers in Urdu literature. His unique style of writing has earned him a distinct status. This paper studies the religious symbols and elements in his famous travelogue "BajangĀmad". The study finds that the writer has beautifully depicted the religious elements and symbols of Islamic civilization and culture. “BajangĀmad” is one of the few books that received commendation on a large scale. Renowned critics of Urdu literature have applauded this book as a great feat achieved by the writer.